The Effectiveness of an Islamic Group Guidance Program in Developing Students’ Positive Mindset and Resilience - Mardhatillah, Mardhatillah; Darimis, Darimis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aims to evaluate the effectiveness of Islamic group guidance programs in developing positive mindsets and self-resilience in students through a literature review. The study was conducted by analyzing journals, scientific books, research reports, and theses and dissertations published in the past ten years. The findings indicate that Islamic-based group guidance has a significant impact on improving self-regulation, spiritual awareness, emotional control, positive cognition, and an optimistic orientation toward the future. Spiritual values ​​such as monotheism, trust (Tawakal), patience, and gratitude serve as psychological capital that strengthens students' resilience in facing academic pressure, social conflict, and personal problems. The integration of modern counseling techniques with Islamic principles places students in a supportive, open, and reflective group environment, accelerating the internalization of a growth mindset and adaptive skills. Overall, Islamic group guidance has proven relevant, effective, and has great potential for systematic implementation in both Islamic and general educational institutions.